Subjective Well-Being of Aceh Adolescents after Tsunami: The Meaning of Disaster and Adolescent Happiness - Afiatin, Tina (Faculty of Psychology, Universitas Surabaya, 2009)
The tsunami impact, December 26, 2004 in Aceh left physical, psychological and social injuries to Aceh people, including adolescents. The purpose of this research is to comprehend how the Aceh adolescents explain the tsunami and the impact to their lives. The qualitative research was con- ducted in Banda Aceh three and a half years after the tsunami with the phenomenology method for two months. Results indicated that the tsunami was differently interpreted by Aceh adolescents. The difference was influenced by their background including, their family life, personality and coping styles. Cohesiveness and family strength was influential to the individual susceptibility to- ward the tsunami impact. The sense of independence, optimistic, social sensitivity and religiousity made them stronger in facing the tsunami impact. The Aceh adolescent happiness after tsunami was greatly influenced by the individual way to interpret happiness and to get the source of happi- ness. Dampak Tsunami, 26 Desember, 2004 di Aceh meninggalkan luka fisik, psikologis, dan social pada masyarakat Aceh, termasuk para remajanya. Tujuan penelitian ini adalah memahami bagai- mana remaja Aceh memaknai tsunami dan dampaknya terhadap kehidupannya. Penelitian kualita- tif dilaksanakan di Banda Aceh tiga setengah tahun setelah tsunami dengan metode fenomenologi selama dua bulan. Hasil-hasil menunjukkan bahwa tsunami dimaknai berbeda oleh para remaja Aceh. Perbedaan tersebut dipengaruhi latar belakangnya, termasuk kehidupan keluarga, kepriba- dian dan gaya kopingnya. Kohesivitas dan ikatan keluarga berpengaruh terhadap kepekaan indivi- du menghadapi dampak tsunami. Rasa bebas, optimistik, sensitivitas sosial dan religiositas mem- buat mereka lebih kuat dalam menghadapi dampak tsunami. Kebahagiaan remaja Aceh setelah tsunami sangat dipengaruhi bagaimana individu menginterpretasi kebahagiaan dan bagaimana memperoleh sumber kebahagiaan.